Evidence that the 5p12 variant rs10941679 confers susceptibility to estrogen receptor-positive breast cancer through FGF10 and MRPS30 regulation. - Ghoussaini, M; French, J; Michailidou, K; Nord, S; Beesley, J; Canisus, S; Hillman, K; Kaufmann, S; Sivakumaran, H; Moradi Marjaneh, M; Lee, J; Dennis, J; et al. (Elsevier, 2016)
Genome-wide association studies (GWASs) have revealed increased breast cancer risk associated with multiple genetic variants at 5p12. Here, we report the fine mapping of this locus using data from 104,660 subjects from 50 case-control studies in the Breast Cancer Association Consortium (BCAC). With data for 3,365 genotyped and imputed SNPs across a 1 Mb region (positions 44,394,495–45,364,167; NCBI build 37), we found evidence for at least three independent signals: the strongest signal, consisting of a single SNP rs10941679, was associated with risk of estrogen receptor-positive (ER+) breast cancer (per-g allele OR ER+ = 1.15; 95% CI 1.13–1.18; p = 8.35 × 10−30). After adjustment for rs10941679, we detected signal 2, consisting of 38 SNPs more strongly associated with ER-negative (ER−) breast cancer (lead SNP rs6864776: per-a allele OR ER− = 1.10; 95% CI 1.05–1.14; p conditional = 1.44 × 10−12), and a single signal 3 SNP (rs200229088: per-t allele OR ER+ = 1.12; 95% CI 1.09–1.15; p conditional = 1.12 × 10−05). Expression quantitative trait locus analysis in normal breast tissues and breast tumors showed that the g (risk) allele of rs10941679 was associated with increased expression of FGF10 and MRPS30. Functional assays demonstrated that SNP rs10941679 maps to an enhancer element that physically interacts with the FGF10 and MRPS30 promoter regions in breast cancer cell lines. FGF10 is an oncogene that binds to FGFR2 and is overexpressed in ∼10% of human breast cancers, whereas MRPS30 plays a key role in apoptosis. These data suggest that the strongest signal of association at 5p12 is mediated through coordinated activation of FGF10 and MRPS30, two candidate genes for breast cancer pathogenesis.